A cohort analysis of breast cancer, uterine corpus cancer, and childbearing pattern in Norwegian women. Issue 3 (September 1990) - Tretli, S; Haldorsen, T
Abstract : STUDY OBJECTIVE–The aim was to study the influence of childbearing pattern on the incidence of breast cancer and uterine corpus cancer. DESIGN–This was an ecological study of birth cohorts of women. SETTING–The study was population based, involving the whole of Norway. PARTICIPANTS–The participants were Norwegian women born between 1890 and 1944. MEASUREMENTS AND MAIN RESULTS–Age specific fertility rates and age specific incidence rates for different birth cohorts were analysed by an age-cohort-period model where quantitative indices of the childbearing pattern substituted the cohort component. The 1890-94 birth cohort had the most favourable childbearing pattern with regard to the risk of breast cancer as well as uterine corpus cancer. The least favourable pattern was in the 1910-14 cohort for breast cancer and the 1940-44 cohort for uterine corpus cancer. In the analysis it is estimated that about 15% of the increase in incidence of breast cancer from 1955 to 1984 may be attributed to changes in the childbearing pattern of the cohorts under study. For cancer of the uterine corpus the corresponding fraction is about 27%. CONCLUSIONS–The study reveals that changes in childbearing pattern may explain a certain fraction of the observed increase in breast and uterine corpus cancer in Norway in the last 30 years, but the largest fraction must be accounted for by other factors.